Clinical Characteristics and Self-Harm in Forensic Psychiatric Patients - Laporte, Natalie; Ozolins, Andrejs; Westling, Sofie; Westrin, Åsa; Wallinius, Märta (Frontiers in Psychiatry, 2021)
Self-harm, comprising non-suicidal self-injury and suicide attempts, is a serious and potentially life-threatening behavior that has been associated with poor life quality and an increased risk of suicide. In forensic populations, suicide is one of the leading causes of death, and rates five to ten times higher than in the general population have been reported. Aside from associations between self-harm and mental disorders, knowledge on self-harm in forensic psychiatric populations is limited. The purpose of this study was to characterize the clinical needs of a cohort of forensic psychiatric patients, including self-harm and its covariates. Participants (N = 98) were consecutively recruited from a cohort of forensic psychiatric patients in Sweden from 2016 to 2020. Data were collected through file information, self-reports, and structured interviews. Results showed that self-harm was common among the participants, more than half (68.7%) of whom had at some point engaged in self-harm. The most common methods of non-suicidal self-injury were banging one’s head or fist against a wall or other solid surface and cutting, and the most common method of suicide attempt was hanging. The most prominent functions of non-suicidal self-injury among the participants were intrapersonal functions such as affect regulation, self-punishment, and marking distress. Self-harm in general was associated to neurodevelopmental disorders (p=.014, CI= 1.23-8.02, OR=3.14) and disruptive impulse-control and conduct disorders (p=.012, CI= 1.19-74.6, OR=9.41), with reservation to very wide confidence intervals. Conclusions drawn from this study are that self-harm was highly prevalent in this sample and seems to have similar function in this group of individuals as in other studied clinical and non-clinical groups.